A Therapeutic Tutoring Program for Children with Psychogenic Learning Disabilities - West, Malcolm (Canadian Journal of Counselling and Psychotherapy, 2012)
This article contends that intervention in psychogenic learning problems must be two-fold. First, therapy is directed toward changing the child's ineffective personal styles where these interfere with learning. Second, tutoring is provided to ameliorate specific knowledge deficits. Traditionally, these two aspects of treatment have been carried out by two different professionals, the therapist and the teacher. The therapeutic- tutoring program described here has attempted to combine the roles of these two persons into one composite helping role. Real life examples are offered to illustrate the approach.